Precast Concrete Sandwich Panel As A Building System - AbdelGhani, Benayuone (2003)
Precast Concrete Sandwich Panels (PCSP) that act as load bearing elements are structurally and thermally efficient building elements with potential for use as an I Industrialised Building System (IBS). The study aims to investigate all issues related to structural performance of PCSP. The strength characteristics of PCSP under imposed loads with both wythes being structural wythes were established and the condition for achieving composite behaviour was examined. Although it is possible to use any conventional flooring system with the use of PCSP as walling elements, the structural behaviour of PCSP under lateral load was also studied so that PCSP can be adopted as flooring elements. This helps to reduce the number of different types of elements necessary in a building. . A study on typical connections between PCSP elements was alsd undertaken. Under axial and eccentric loads, an experimental program consisting of twelve specimens with different heights was carried out. The theoretical investigation consists of two theoretical formulations namely, classical expressions and Finite Element Method (FEM). Comparison between non-linear FEM proposed models and experimental data was made in order to validate the models.